Enhanced Biosynthesis of Fatty Acids Is Associated with the Acquisition of Ciprofloxacin Resistance in Edwardsiella tarda - Yu-bin Su; Su-fang Kuang; Jin-zhou Ye; Jian-jun Tao; Hui Li; Xuan-xian Peng; Bo Peng (mSystems, 2021)
Edwardsiella tardaE. tarda